Preparation and Property Enhancement of Hydroxyapatite/ Poly(vinyl pyrrolidone) Nanocomposites - Wu, Yun; Yang, Benhong; Li, Meng; Liu, Dan (Asian Journal of Chemistry, 2013)
A series of noval organic-inorganic nanocomposite materials of hydroxyapatite/poly(vinyl pyrrolidone) were synthesized by in situ copolymerization of modified inorganic nanoscale hydroxyapatite and poly(vinyl pyrrolidone). The hydroxyapatite/poly(vinyl pyrrolidone) nanocomposites were characterized by scanning electronic microscope, X-ray diffraction and Fourier transform infrared analysis. The thermogravimetric analysis and differential scanning calorimetry results showed that the thermal properties of hydroxyapatite/poly(vinyl pyrrolidone) nanocomposites were significantly improved compared with the mother poly(vinyl pyrrolidone) polymers.